Analisis Keuntungan Pemasaran Bunga Mawar Potong (Rosa Hybrida L.) Di Kecamatan Bandungan Kabupaten Semarang - Anandya, Annisa; Wahyuningsih, Sri; Subantoro, Renan; Prabowo, Rossi (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Rose (Rosa hybrida L.) is a popular cut flower species in Indonesia. Roses have a high enough economic and social value to be used as a commercial trade commodity. This suggests that rose cultivation is an agribusiness-oriented business with very bright prospects. This study aims to determine the turnover, revenue, marketing costs, profit and R/C ratio of cut roses sales in Bandungan Semarang Flower Market. The basic method used in this research is quantitative descriptive method. The sampling technique used is saturated sampling method technique or census. With the number of respondents as many as 10 traders. The results of the research of the business of selling cut roses issued an average turnover of Rp.25,000,000, revenue of Rp.15.000,000 with marketing costs of Rp.7.225,000 so as to obtain a profit of Rp.7.775,000 / month. The average R / C ratio value of the business of selling cut roses is 2.08, which means that the business of selling cut roses is feasible because R / C > 1.